2021
DOI: 10.1021/acs.macromol.1c01930
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Alternating Sequences in Methyl Methacrylate/n-Butyl Acrylate Copolymers Prepared by Atom Transfer Radical Polymerization

Abstract: Copolymers of n-butyl acrylate/methyl methacrylate (BA/MMA) with certain compositions were recently proposed as self-healing materials due to "key-and-lock" interchain interactions of alternating sequences. This inspired us to analyze by numerical simulations the formation of heterosequences in BA/MMA copolymers prepared by atom transfer radical polymerization (ATRP). Stochastic Monte Carlo and deterministic simulations using numerical integration of differential equations showed that the highest contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
(70 reference statements)
0
30
0
1
Order By: Relevance
“…We recently reported the synthesis of SiO 2 - g -PBA- grad -PMMA particle brushes with various grafting densities using a semibatch copolymerization activator regenerated by electron transfer (ARGET) surface-initiated atom transfer radical polymerization (SI-ATRP) . The deliberate variation of monomer feed ratio and conversion ratio was shown to facilitate the synthesis of gradient and random copolymer brush particle architectures . A detailed analysis of the distribution of various comonomer sequences in the gradient and random copolymers was also recently reported .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported the synthesis of SiO 2 - g -PBA- grad -PMMA particle brushes with various grafting densities using a semibatch copolymerization activator regenerated by electron transfer (ARGET) surface-initiated atom transfer radical polymerization (SI-ATRP) . The deliberate variation of monomer feed ratio and conversion ratio was shown to facilitate the synthesis of gradient and random copolymer brush particle architectures . A detailed analysis of the distribution of various comonomer sequences in the gradient and random copolymers was also recently reported .…”
Section: Resultsmentioning
confidence: 99%
“…The deliberate variation of monomer feed ratio and conversion ratio was shown to facilitate the synthesis of gradient and random copolymer brush particle architectures . A detailed analysis of the distribution of various comonomer sequences in the gradient and random copolymers was also recently reported . Here, two series of SiO 2 - g -PBA- grad -PMMA were prepared, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The use of dipolar interactions eliminates chemical and physical alterations and enables multiple recoveries without external intervention . Although ideally alternating MMA/nBA sequences are desired, semi-batch programmed monomer feeding will enhance the amount of alternating sequences …”
Section: Results and Discussionmentioning
confidence: 99%
“…Numerical simulations of PMMA/P n BA copolymers prepared by ATRP under various conditions revealed that the number of alternating sequences is maximized for a statistical copolymer with 1/1 MMA/ n BA composition. [ 92 ] Thus, a feeding strategy in which MMA is continuously fed into the polymerization mixture to obtain statistical copolymers should provide materials exhibiting more effective self‐healing ability.…”
Section: The 12 Principles Of Green Chemistry and Their Implementatio...mentioning
confidence: 99%